Preferensi Parasitoid Trichogrammatoidea spp. yang Memarasit Telur Penggerek Buah Merah Jambu Pectinophora gossypiella Saunders (Lepidoptera; Gelechiidae) terhadap Beberapa Inang - Dwi Adi Sunarto; Nurindah Nurindah; Sujak Sujak (Universitas Gadjah Mada, 2005)
Pink bollwonn Pectinophora gossypiella Saunders (Lepidoptera: Gelechiidae), is one of the key pests of cotton. Exploration of its egg parasitoids in East Java, yields Trichogrammatoidea spp. The research objective are to study host acceptance of the parasitoids to several levels of host age and host species for a consideration of selection in using the parasitoids as candidates of biocontrol agent of pink bollworm. The study was carried out in Biocontrol Laboratory of Indonesian Tobacco and Fiber Crops Research Institute (IToFCRI) from April to December 2002 with laboratory condition (T: 25 - 27°C; RH: 65-70%). The treatments consist of combinations of the parasitoid origin (Trichogrammatoidea sp A and Trichogrammatoidea sp L); host species (eggs of Corcyra cephalonica, P. gossypiella, and Helicoverpa armigera) and host ages (1, 2 and 3 days). The number of replicates is 10. Preference level was assessed by using continuous observation method. Trichogrammatoidea sp A is most preferred to P. gossypiella eggs, significantly different with that of C. cephalonica and H. armigera eggs. Host preference of Trichogrammatoidea sp L to P. gossypiella and C. cephalonica eggs is not significantly different and higher than that of H. armigera eggs. Both parasitoid species have no different preference to P. gossypiella and H. armigera eggs, however, Trichogrammatoidea sp L has a higher preference to C. cephalonica eggs than Trichogrammatoidea sp A. Host preference of both species was not affected by the age of all three species of host eggs.